Requerimientos para la medición de indicadores de estrés invasivos y no invasivos en producción animal - Sanmiguel Plazas, Rosa Angélica (2018)
This review presents the main requirements for measuring multimodal welfare indicators in production animals, from production parameters to physiological parameters, categorized as noninvasive indicators and invasive indicators. It is intended to generate a collection of ideas so that the researcher, in accordance with the limitations, conditions and scope of its resources, evaluate animal welfare for academic purposes, research and optimization of the production and marketing of the final products in a livestock production system.